Novas estratégias cromatográficas visando a recuperação e purificação de proteínas do soro de sangue humano e do leite bovino - Sousa, Paula Luciana Rodrigues de (2019)
Proteins are abundant molecules in nature and can be used for several purposes, in fields such as health, food, textiles, cosmetics, among others. Thus, the industry of these sectors has sought more efficient processes to obtain proteins in the purified form. In this context, the present work aims to investigate the use of the Capto MMC multimodal resins, Streamline SP ion exchange, Streamline DEAE and hydrophobic Phenyl Sepharose in the purification processes of proteins from human blood and bovine milk serum. Therefore, experimental designs were carried out to obtain the conditions of adsorption and elution with IgG standard proteins, which were reproduced in human serum samples. In parallel, the BSA adsorption and elution conditions were obtained through new experimental designs. In the IgG and BSA delineations, the pH, Ct and Csal parameters were evaluated. A pretreatment was carried out on bovine milk serum samples to remove impurities and protein concentration, making it possible to analyze them in fixed bed. Serum samples from bovine milk were evaluated through a new experimental design, where the effects of pHads, pHelu and Telu parameters were verified. The obtained experimental conditions were applied in the ion exchange resins Streamline SP and DEAE in expanded bed. The resin with hydrophobic interaction Phenyl Sepharose was studied in fixed bed to verify the efficiency of these interactions when used separately. Proteins were quantified by Bradford and their separation analyzed by SDS-PAGE electrophoresis under non-reducing conditions. Assays with IgG and BSA proteins showed that the Capto MMC multimodal resin presented high adsorption capacity, obtaining 549.2 and 380.16 mg•g-1, respectively. The design models were significant. As for the elution, although the design models were not significant, the conditions with better IgG elution performance when reproduced in human serum samples obtained excellent results, as it was able to recover only IgG and HSA in the elution step, removing other contaminants found in human serum. In the case of bovine milk serum samples, the results showed that, Capto MMC resin presented high selectivity for BSA proteins (66 kDa) and β-Lg (30 kDa) dimer. In the expanded bed assays, the combined use of the Streamline SP and DEAE ion exchange resins showed selectivity for the β-Lg (18 kDa) protein under the conditions worked. However, β-Lg protein (18 kDa) was only isolated when used in the Streamline SP and Phenyl Sepharose sequence. Thus, it was found that ion exchange and hydrophobic interactions became more efficient in the purification processes of bovine milk whey proteins when used separately. However, the use of Capto MMC resin showed selectivity for proteins BSA and β-Lg dimer, being able to remove contaminants in the studied matrixes.